Verificación del efecto foto eléctrico con luz ultravioleta - Marquez, A. L. (Revista Científica, 2011)
From the point of view of student development is an experiment to verify the photoelectric effect with a simple assembly to clarify questions concerning this effect and wave frequencies which can occur, just as there is the mathematical connection between the equation Einstein and the equation of work based on the electron charge to analyze the feasibility of experimental quantification of this check.